Cooperative Targets of Combined mTOR/HDAC Inhibition Promote MYC Degradation - Simmons, John K. (Mol Cancer Ther, 2017)
Cancer treatments often require combinations of molecularly targeted agents to be effective. mTORi (rapamycin) and HDACi (MS-275/entinostat) inhibitors have been shown to be effective in limiting tumor growth, and here we define part of the cooperative action of this drug combination. More than 60 human cancer cell lines responded synergistically (CI<1) when treated with this drug combination compared to single agents. In addition, a breast cancer patient-derived xenograft, and a BCL-XL plasmacytoma mouse model both showed enhanced responses to the combination compared to single agents. Mice, bearing plasma cell tumors lived an average of 70 days longer on combination treatment compared to single agents. A set of 37 genes cooperatively affected (34 down-regulated; 3 up-regulated) by the combination responded pharmacodynamically in human myeloma cell lines, xenografts, and a P493 model, and were both enriched in tumors, and correlated with prognostic markers in myeloma patient datasets. Genes down-regulated by the combination were overexpressed in several untreated cancers (breast, lung, colon, sarcoma, head and neck, myeloma) compared to normal tissues. The MYC/E2F axis, identified by upstream regulator analyses and validated by immunoblots, was significantly inhibited by the drug combination in several myeloma cell lines. Furthermore, 88% of the 34 genes downregulated have MYC binding sites in their promoters, and the drug combination cooperatively reduced MYC half-life by 55% and increased degradation. Cells with MYC mutations were refractory to the combination. Thus, integrative approaches to understand drug synergy identified a clinically actionable strategy to inhibit MYC/E2F activity and tumor cell growth in vivo.